2011
DOI: 10.1002/elsc.201000135
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of a Trigonopsis variabilis D‐amino acid oxidase variant F54Y for oxidative deamination of cephalosporin C

Abstract: Trigonopsis variabilis D‐amino acid oxidase (TvDAAO) is an enzyme used in the industrial bioconversion of cephalosporin C (CPC) into 7‐aminocephalosporanic acid, a crucial biosynthetic nucleus for a wide spectrum of semi‐synthetic cephem antibiotics. Using homology modeling and site‐directed mutagenesis, we have previously shown that the TvDAAO variant F54Y possesses improved catalytic activity and thermostability. To further explore its industrial application, the conditions for immobilization of the enzyme w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Purity of the enzyme was analysed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis, and its concentration was determined by Bradford assay. The catalytic activity of the purified enzyme was determined by measuring the formation of GL-7-ACA at 22°C with agitation [ 3 ]. One mL of the reaction mixture contained 20 μg TvDAAO F54Y/W113Y variant, 5 mM cephalosporin C, and 50 mM sodium phosphate (pH 7.5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purity of the enzyme was analysed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis, and its concentration was determined by Bradford assay. The catalytic activity of the purified enzyme was determined by measuring the formation of GL-7-ACA at 22°C with agitation [ 3 ]. One mL of the reaction mixture contained 20 μg TvDAAO F54Y/W113Y variant, 5 mM cephalosporin C, and 50 mM sodium phosphate (pH 7.5).…”
Section: Methodsmentioning
confidence: 99%
“…A single amino acid substitution at the 54th position of TvDAAO from phenylalanine (F) to tyrosine (Y) resulted in a 6-fold improvement in catalytic activity towards CPC and in thermostability after heat treatment at 55°C [ 2 ]. The potential application of the TvDAAO F54Y variant in the antibiotics industry as a simple and efficient biocatalyst was evaluated [ 3 ]. To further elucidate the structural basis of the catalytic activity and thermostability of TvDAAO F54Y, we investigated the role of the 113th amino acid residue (tryptophan, W113) that locates near the substrate binding cleft.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that entrapment in Ca-alginate matrix appeared to be an efficient method for antibiotics industry. Because of the availability of Ca-alginate and simplicity of the immobilization technique, this production can be considered economically viable (Wong et al 2011).…”
Section: Pharmaceuticalmentioning
confidence: 99%
“…Encapsulation using polyelectrolyte complexation has found wide applications in various industries such as food industry, pharmaceutical, enzyme production, and pulp and paper . Encapsulation via calcium alginate beads has been studied extensively due to simple preparation, inexpensive process, and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%